Circadian pacemaker neurons change synaptic contacts across the day - Gorostiza, Ezequiel Axel (2014)
Daily cycles of rest and activity are a common example of circadian control of physiology. In Drosophila, rhythmic locomotor cycles rely on the activity of 150-200 neurons grouped in seven clusters [1, 2]. Work from many laboratories points to the small ventral lateral neurons (sLNvs) as essential for circadian control of locomotor rhythmicity [3-7]. sLNv neurons undergo circadian remodeling of their axonal projections, opening the possibility for a circadian control of connectivity of these relevant circadian pacemakers [8]. Here we show that circadian plasticity of the sLNv axonal projections has further implications than mere structural changes. First, we found that the degree of daily structural plasticity exceeds that originally described [8], underscoring that changes in the degree of fasciculation as well as extension or pruning of axonal terminals could be involved. Interestingly, the quantity of active zones changes along the day, lending support to the attractive hypothesis that new synapses are formed while others are dismantled between late night and the following morning. More remarkably, taking full advantage of the GFP reconstitution across synaptic partners (GRASP) technique [9], we showed that, in addition to new synapses being added or removed, sLNv neurons contact different synaptic partners at different times along the day. These results lead us to propose that the circadian network, and in particular the sLNv neurons, orchestrates some of the physiological and behavioral differences between day and night by changing the path through which information travels.